La constitucionalidad de la existencia de las cajas Municipales en el Sistema de Intermediación Financiera - Pomayay Bravo, Luisa Alejandra (2018)
ABTRACT The research work "The Constitutionality of the existence of the Cajas Municipales de Ahorro y Crédito (CMAC) in the financial intermediation system", deals with the existence of the CMACs owned by the municipalities and the role they play in the sector financial; During the development of the investigation, it is analyzed if the activities carried out by the CMACs fall within the subsidiarity allowed by the State; Its objective is the analysis of the legal nature of the CMACS, the determination of the role it plays in Peruvian society and in the financial system; and its correspondence with the current constitutional order. The investigation starts by analyzing the historical, political, economic context that gave rise to the municipal funds, all the normative bodies that were published after its creation; their growth indicators and the role they have within the financial sector were analyzed, as well as whether the activity carried out by these companies has a subsidiary function and whether it is in accordance with the current constitutional order. The results obtained are that the CMACs are companies of the financial system of private law, owned by the municipalities, whose presence is necessary for the development of the country, due to the promotion of savings and the granting of credit for people part of the financial inclusion, Therefore, apart from being a fundamental part of the financial sector, it is a company whose presence is in accordance with the constitutional order for the social purpose it pursues.